Solusi Pencegahan Permasalahan Moralitas dalam Masyarakat - James, James (Universitas Medan Area, 2015)
Nowadays, Indonesia is facing the multidimensional crisis in economy, politic, security, culture, religion, living space, and the other field. The experts say that all of those crisis that we face in Indonesia is rooted from nation morality and ethic crisis. Eventually, the morality problems are not only heard and theorized, but more than that, the morality problems are the problems that need to be thought together and how to solve them. Since the variety of tribes, religion, and territory in Indonesia, it needs some variety of ways to solve the morality problems deal with each community. The writer tries to see how to solve the general morality problems, and hopefully can be a useful orientation to all of us.Â